1994
DOI: 10.2337/diab.43.8.1027
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Dependent Vascular Effects of Insulin and Insulin-Like Growth Factor I in the Perfused Rat Mesenteric Artery and Aortic Ring

Abstract: Insulin and insulin-like growth factor I (IGF-I) exhibit vasoactivity. To examine the role of the endothelium in mediating the vascular responses to insulin and IGF-I, we exposed both isolated intact rat mesenteric arteries and rat aortic rings to these growth factors in the presence and absence of endothelium. Perfusion of rat mesenteric arteries with insulin, IGF-I, or IGF-II resulted in the potentiation of arginine vasopressin (AVP)-induced vasoconstriction. Of these growth factors, IGF-I was the most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 0 publications
3
66
0
2
Order By: Relevance
“…The mechanism by which IGF-I exerts this effect is through the synthesis of nitric oxide. In fact the co-infusion of an analog of arginine blocks the response [20][21][22]. These data provide an opportunity to expand on the role of NO in the mediation of some relevant clinical events related to GHD.…”
mentioning
confidence: 83%
“…The mechanism by which IGF-I exerts this effect is through the synthesis of nitric oxide. In fact the co-infusion of an analog of arginine blocks the response [20][21][22]. These data provide an opportunity to expand on the role of NO in the mediation of some relevant clinical events related to GHD.…”
mentioning
confidence: 83%
“…23 Besides, IGF-1 has been demonstrated to function as a vasodilator that is similar to those of insulin. 18 Therefore, the increased IGF-1-induced aortic vasorelaxation in obese Zucker rats might imply that the impaired insulinmediated vasorelaxation appear to be counteracted with the upregulated IGF-I-mediated vasorelaxation in obese rats. We speculate that our findings in obese Zucker rats could be useful models for investigating similar vascular pathophysiologic conditions occurred in obese animals or obese human.…”
Section: Disscussionmentioning
confidence: 99%
“…16 In experimental animals, insulin has differential effects in different vascular beds, exerting vasorelaxant effects on the femoral, aortic, coronary and tail vasculature 16,17 Insulin-like growth factor-1 has effects on the regulation of vascular tone that are similar to those of insulin, with regional differences in vasorelaxant responses. 18 The endothelium-derived relaxing factor, nitric oxide (NO), appears to be an important mediator of insulininduced and IGF-1-induced vascular relaxations. 17,19,20 Both insulin and IGF-1 stimulate NO production and diminish in vivo and in vitro vascular contractilities in intact vessels.…”
Section: Introductionmentioning
confidence: 99%
“…29 The receptor inhibitor candesartan was associated with 40% less new-onset diabetes in subjects with heart failure in 3 ethnic groups (CHARM), 30 and the receptor inhibitor vasartan was associated with 23% less new-onset diabetes in subjects with HTN (VALUE). 31 Physiological studies have revealed a number of potential mechanistic links between IR and elevated BP: activation of renal sodium retention and the sympathetic nervous system by hyperinsulinemia, the usual concomitant of IR; 32,33 resistance of blood vessels to the vasodilatory effects of insulin; 34 decreased ability of insulin to stimulate skeletal muscle blood flow; 35 and altered ion transport mechanisms leading to both IR and HTN. 36,37 Cause-effect relationships between these factors and HTN remain to be established.…”
Section: Guo Et Al Hypertension Genes Affect Insulin Resistancementioning
confidence: 99%